ATP2B1-AS1 Promotes Cerebral Ischemia/Reperfusion Injury Through Regulating the miR-330-5p/TLR4-MyD88-NF-κB Signaling Pathway - Wang, Lei; Tan, Ying; Zhu, Ziyu; Chen, Jun; Sun, Qiang; Ai, Zhibin; Ai, Chunqi; Xing, Yu; He, Guohou; Liu, Yong (Frontiers in Cell and Developmental Biology, 2021)
We aim to explore the expression and function of Long non-coding RNA (lncRNA) ATP2B1-AS1 in cerebral ischemia/reperfusion (I/R) injury. In this study, we established a middle cerebral artery occlusion/reperfusion (MCAO/IR) rat model and an OGD/R PC12 cell model to evaluate the expression and the role of ATP2B1-AS1 in the cerebral I/R injury. We found that the expression of ATP2B1-AS1 was up-regulated in both in vitro and in vivo cerebral I/R injury models. Knockdown of ATP2B1-AS1 increased the cell viability, inhibited apoptosis, and decreased the expressions of inflammation cytokines. The target of ATP2B1-AS1 was predicted and validated to be miR-330-5p. MiR-330-5p abrogated the regulatory effect of ATP2B1-AS1 on cell viability, apoptosis, and cytokines of OGD/R PC12 cells. Furthermore, the results showed miR-330-5p targeted TLR4, which was also up-regulated in the infarcted area of MCAO/IR rats and the OGD/R PC12 cells. Over-expression of ATP2B1-AS1 increased the expressions of TLR4, MyD88, and NF-кB p65 of OGD/R PC12 cells, while the effect of ATP2B1-AS1 was abrogated by miR-330-5p. In addition, knockdown of ATP2B1-AS1 decreased the latency time, increased the time of passing the platform position, reduced the cerebral infarct volume, decreased neurological deficit scores, and reduced the number of damaged neurons of MCAO/IR rats that subjected to the Morris water maze test. Taken together, our study indicates that ATP2B1-AS1 may be an attractive therapeutic target for the treatment of cerebral ischemic injuries.